Role of zinc-coated urea fertilizers in improving nitrogen use efficiency, soil nutritional status, and nutrient use efficiency of test crops - Abdullah, Bilal; Niazi, Muhammad Bilal Khan; Jahan, Zaib; Khan, Obaid; Shahid, Ameen; Shah, Ghulam Abbas; Azeem, Babar; Iqbal, Zahid; Mahmood, Abid (Frontiers in Environmental Science, 2022)
Rise in global population, urbanization, and desertification pushing the farming community towards intensive cropping to meet the augmented food demands with consequent exhaustion of soil’s nutritional status and fertility. In recent times, environmental pollution and cost of crop production have been enhanced due to excessive and inefficient use of nitrogenous fertilizers. As an abatement strategy, seven different coated urea fertilizers namely Gelatin-coated (G), Zinc oxide with Gelatin-coated (ZnOG), Zinc oxide-coated (ZnO), sonicated Zinc oxide-coated (ZnO-Son), Zinc oxide with molasses-coated (ZnOM), Zinc sulphate with molasses-coated (ZnSM) and Zinc sulphate-coated (ZnS) were prepared in a fluidized bed coater. The coated samples were characterized through XRD, SEM and FTIR techniques while crushing strength test was carried out to assess the impact of inventory operations on physical integrity of coated prills. Pot tests with Ryegrass as test crop was carried out to evaluate effect of coating urea fertilizers on yield, and nitrogen (N) and zinc (Zn) uptake in order to enhance nitrogen use efficiency and reduce pollution. Our results suggest that the affinity between urea surface and coating materials were of physical nature. All zinc oxide or gelatin coated treatments significantly increased the dry matter yield, nitrogen uptake, apparent nitrogen recovery (ANR), zinc uptake and apparent zinc recovery (AZnR). ZnOG proved best sample in terms of balancing soil chemical properties with improved soil nutrition and producing best with plant yield (94% higher than UC), N uptake (75% higher than UC), Zn uptake (450% higher than UC) and Nitrogen use efficiency (48% vs 23% for UC). Our results suggest that use of such coated fertilizers by farmers can lead to improved agro-ecological and economic scenario by cutting cost of nitrogenous fertilizers.